2011
DOI: 10.1509/jppm.30.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Consumption: Opportunities for Consumer Research and Public Policy

Abstract: This essay explores sustainable consumption and considers possible roles for marketing and consumer researchers and public policy makers in addressing the many sustainability challenges that pervade the planet. Future research approaches to this interdisciplinary topic must be comprehensive and systematic and would benefit from a variety of different perspectives. There are several opportunities for further research; the authors explore three areas in detail. First, they consider the inconsistency between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
510
0
26

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 617 publications
(545 citation statements)
references
References 52 publications
9
510
0
26
Order By: Relevance
“…It was suggested that people in their roles as citizens rather than shoppers were perhaps more susceptible to sustainable consumption discourse. This also is supported by findings from previous research that emphasises that addressing individuals as citizens invokes values of responsibility, community and moderation (Prothero, Dobscha et al 2011).…”
Section: Nordic Insightssupporting
confidence: 80%
“…It was suggested that people in their roles as citizens rather than shoppers were perhaps more susceptible to sustainable consumption discourse. This also is supported by findings from previous research that emphasises that addressing individuals as citizens invokes values of responsibility, community and moderation (Prothero, Dobscha et al 2011).…”
Section: Nordic Insightssupporting
confidence: 80%
“…Whilst it might be unethical to advocate marketers' involvement in such programs, there are clear opportunities for non-profit organizations to link up with environmental education lessons [34], thus providing the raw material for the potential transfer of knowledge from adolescent to parent. We echo the point of Prothero et al [69] who question how such educational initiatives impact on how children think and act from a consumer perspective, calling for more research in this field.…”
Section: Public Policy Contributionsmentioning
confidence: 70%
“…As Prothero et al point out, participating in CSR is generally very socially and ecologically sustainable [122]. This makes the perceived value of sustainability, as it regards CSR issues, a potentially key factor in the willingness of people to consume more consciously.…”
Section: Contextual/market Levelmentioning
confidence: 99%